Anthropology at the basis of medicine: an old and up to date debate - Catananti, Cesare (Medicina e Morale, 1996)
The history of medicine has been constantly punctuated by a lively debate on what medical knowledge is, on what the correct practice of the knowledge is, and on whether and how that practice can be integrated from an anthropological point of view. This constant call for the humanization of medical assistence betrays the deep need for medicine which concentrates on man and not on his disease. This is a very old need since already in the 5th century B.C. the differences between the medical school of Cos and that of Cnido concerned exactly this question. After providing a brief history of medicine, from this point of view, the author shows how with the identification and the spreading of the scientific and quantitative method, since the 17th century the tecnical, economical and sociological aspects have prevailed over the aspect regarding relationships. While in his opinion it is in the search for psycho-biological integration that the doctus et expertus physician in able to assert his sapientia, scientia and sapientia cordis which are intertwined. In this way the physician's relationship with his patient will be characterized not by a paternalistic of authoritarian attitude but by equal empathy. Therefore it is a question of creating a tecnè which should rest harmoniously on two pillars: one of scientific knowledge and one of humanitarian ethos, therefore medicine making anthropology and technology coincide.